2015
DOI: 10.1097/ccm.0000000000000867
|View full text |Cite
|
Sign up to set email alerts
|

Characterizing Degree of Lung Injury in Pediatric Acute Respiratory Distress Syndrome

Abstract: PaO2/FIO2 and oxygenation index 24 hours after meeting acute respiratory distress syndrome criteria accurately stratified outcomes in children. Initial values were not helpful for prognostication. Definitions of acute respiratory distress syndrome may benefit from addressing timing of oxygenation metrics to stratify disease severity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
138
3
4

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 100 publications
(155 citation statements)
references
References 34 publications
9
138
3
4
Order By: Relevance
“…9 More recently, the PALICC OI-based severity stratification categories of PARDS were assessed and validated to indicate the highest risk of death in the severe category with OI>16. 10 Our study expands upon previously reported data on increased mortality risk with lower levels of OI than have been historically used for ECMO candidacy. 11 It also supports and provides additional validation of PALICC PARDS OI thresholds for increased risk of death.…”
supporting
confidence: 67%
See 3 more Smart Citations
“…9 More recently, the PALICC OI-based severity stratification categories of PARDS were assessed and validated to indicate the highest risk of death in the severe category with OI>16. 10 Our study expands upon previously reported data on increased mortality risk with lower levels of OI than have been historically used for ECMO candidacy. 11 It also supports and provides additional validation of PALICC PARDS OI thresholds for increased risk of death.…”
supporting
confidence: 67%
“…In addition, use of lower OI's for entry criteria into clinical studies of pediatric respiratory failure may also be warranted. 6,[10][11][12][13] This threshold OI finding warrants further investigation with larger data sets from multiple centers. Review of the patient EMR had limited capability in calculating OI.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Yehya et al 14 examined subjects in a single center and compared them with some of the findings in the PALICC reports. The timing of their study, appearing at about the same time as the PALICC supplement, brings some validation to the recommendations by the PALICC group.…”
Section: Characterizing Acute Lung Injurymentioning
confidence: 99%